Hermeneutika Fiqih Otentik Gus Dur di Indonesia - Moh Dahlan (Faculty of Sharia, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2017)
This study aims to examine the existence of the hermeneutic thinking of ijtihad and authentic jurisprudence of Gus Dur in Indonesia. By using Martin Heidegger's hermeneutics, this study produces two conclusions: First, the authentic hermeneutic paradigm of ijtihad Gus Dur seeks to establish a dialectic between the discourse of the past text and the interpreter's current discourse so that the law of fiqih can produce the ultimate benefit of the people. Secondly, the authentic jurisprudence of Gus Dur has given the discourse of new fiqh relevant to the current development of polygamy law, marriage, zakat and the Islamic education system grounded in accordance with Indonesian culture, not Arab culture, so that he wants the earthing of legal discourse of jurisprudence instead of Arabization .